Pharmacogenetic Review: Germline Genetic Variants Possessing Increased Cancer Risk With Clinically Actionable Therapeutic Relationships - Saugstad, Austin A.; Petry, Natasha; Hajek, Catherine (Frontiers in Genetics, 2022)
As our understanding of genomics and genetic testing continues to advance, the personalization of medical decision making is progressing simultaneously. By carefully crafting medical care to fit the specific needs of the individual, patients can experience better long-term outcomes, reduced toxicities, and improved healthcare experiences. Genetic tests are frequently ordered to help diagnose a clinical presentation and even to guide surveillance. Through persistent investigation, studies have begun to delineate further therapeutic implications based upon unique relationships with genetic variants. In this review, a pre-emptive approach is taken to understand the existing evidence of relationships between specific genetic variants and available therapies. The review revealed an array of diverse relationships, ranging from well-documented clinical approaches to investigative findings with potential for future application. Therapeutic agents identified in the study ranged from highly specific targeted therapies to agents possessing similar risk factors as a genetic variant. Working in conjunction with national standardized treatment approaches, it is critical that physicians appropriately consider these relationships when developing personalized treatment plans for their patients.